In vitro activation of the transcription factor gamma interferon activation factor by gamma interferon: evidence for a tyrosine phosphatase/kinase signaling cascade. - Igarashi, K (1993)
Although it has been well documented that the biological activities of gamma interferon (IFN-gamma) are initiated through interaction with its cell surface receptor, the signal transduction mechanisms which mediate the effects of this cytokine have remained unclear. In order to facilitate a better understanding of IFN-gamma signaling, we have designed an assay using human fibroblast cell homogenates in which IFN-gamma activates the formation of the IFN-gamma activation factor (GAF) transcription complex. GAF mediates the rapid transcriptional activation of the guanylate-binding protein gene by IFN-gamma. Activation of GAF in homogenates required ATP, but not Ca2+ or GTP. Fractionation of homogenates indicated that both the pellet (18,000 x g) and the remaining cytoplasmic fraction were required for GAF activation by IFN-gamma. In intact cells and cell homogenates, the activation of GAF was prevented by the specific tyrosine kinase inhibitor genistein. Treatment of GAF-containing nuclear extracts with either monoclonal antiphosphotyrosine antibody or protein tyrosine phosphatase prevented the assembly of the transcription complex, indicating that its formation required phosphorylation of tyrosine residues. Furthermore, the tyrosine phosphatase inhibitors phenylarsine oxide and zinc chloride also inhibited GAF formation in vitro, but only if these agents were added to cell homogenates before IFN-gamma was added. The addition of either agent 5 min after IFN-gamma had no effect. These results provide the first evidence for an IFN-gamma-regulated tyrosine phosphatase/kinase signaling cascade that permits this cytokine to activate the transcription of an early-response gene.